(untitled) (Naturalistic: Jurnal Kajian dan Penelitian Pendidikan dan Pembelajaran, 2024)
The Paradigm of Islamic Religious Education (IRE) with the concept of "Rahmatan Lil Alamin" (mercy to the entire universe) has been a subject of debate and a primary focus from various perspectives. In this view, IRE is seen as a means to understand, interpret, and implement Islamic teachings in a broader and more inclusive context. Various perspectives that emerge encompass aspects such as education, social, and humanitarian concerns. In terms of education, IRE with the "Rahmatan Lil Alamin" paradigm emphasizes the importance of educating individuals with a profound understanding of Islam while also promoting tolerance, mutual understanding, and interfaith cooperation in a pluralistic society. From a social perspective, IRE with this paradigm serves as a tool to promote peace, harmony, and equality in a culturally and religiously diverse society. Moreover, from a humanitarian perspective, "Rahmatan Lil Alamin" emphasizes humanitarian values, justice, and a deep understanding of human rights. Therefore, the IRE paradigm of "Rahmatan Lil Alamin" makes a significant contribution to efforts to create an inclusive, tolerant, and collectively welfare-oriented society.